The Role of Motor Affordances in Visual Working Memory - Diane Pecher (Baltic International Yearbook of Cognition, Logic and Communication, 2014)
Motor affordances are important for object knowledge. Semantic tasks on visual objects often show interactions with motor actions. Prior neuro-imaging studies suggested that motor affordances also play a role in visual working memory for objects. When participants remembered manipulable objects (e.g., hammer) greater premotor cortex activation was observed than when they remembered non-manipulable objects (e.g., polar bear). In the present study participants held object pictures in working memory while performing concurrent tasks such as articulation of nonsense syllables and performing hand movements. Although concurrent tasks did interfere with working memory performance, in none of the experiments did we find any evidence that concurrent motor tasks affected memory differently for manipulable and non-manipulable objects. I conclude that motor affordances are not used for visual working memory.
Keywords: motor affordances; object knowledge; semantic tasks; visual working memory; manipulating objects